Genetically engineered microalgae for enhanced bioactive compounds - Ahmad Kamal, Ahmad Hanafi; Mohd Hamidi, Nor Farahdevah; Zakaria, Muhammad Faiz; Ahmad, Aziz; Harun, Mohd Razif; Chandra Segaran, Thirukanthan; Jusoh, Malinna (Springer Nature, 2024)
Microalgae are naturally rich in carbohydrates, lipids, proteins, pigments, minerals, and vitamins. These metabolites make them a renewable and sustainable source of bioactive compounds in nutraceuticals, food, feed for aquaculture, and biofuels. Genetic engineering of the existing strains remains crucial in utilising and upscaling microalgae-based biorefineries. CRISPR/Cas9, TALENs, ZFNs, and genetic transformation are the established tools utilised in microalgae genetic engineering. The common genetic transformation methods include electroporation, particle bombardment (biolistics), glass-bead agitation, and Agrobacterium-mediated transformation. Expression vectors and promoters are the prerequisites in genetic engineering. The present accessibility of genome sequences and omics datasets from a diverse array of microalgae species holds promise for catalyzing strategic progress in developing a superior microalgae strain suitable for numerous applications. This paper describes the genetic engineering to enhance microalgae biomass and metabolite production, particularly lipids. The advantages and precautions to fulfil the future application of genetically engineered microalgae are also reviewed and addressed.